Optimalisasi Pajak Daerah Untuk Meningkatkan Pendapatan Asli Daerah - Yani, Hera; Martini, Rita; Sarikadarwati, Sarikadarwati (Universitas Muhammadiyah Metro, 2024)
This research aims to determine the influence of the contribution and effectiveness of regional taxes on local revenue in districts/cities in South Sumatra province in 2018-2022. This research uses secondary data originating from the website http://eppid.bpk.go.id in the form of budget realization reports in 17 districts/cities in South Sumatra province. The data collection technique in the research used saturated sampling and the observation unit was 85 samples. The hypothesis testing tool in this research uses Smart-PLS version 4.0. based on the results of partial hypothesis testing, the contribution of regional taxes has no effect on original regional income, the effectiveness of regional taxes has an effect on original regional income, and simultaneously the contribution of regional taxes and the effectiveness of regional taxes have an effect on original regional income.